Jan Čep on Radio Free Europe - Kopecká-Valeská, Olga (Bohemica Olomucensia, 2015)
The article presents memories of Čep's listener and later colleague who after Čep's death became the editor of his texts written for the Radio Free Europe broadcast.
Keywords: Jan Čep; Radio Free Europe; memories; broadcast essays